THE USE OF INTERROGATIVE PRONOUNS IN ENGLISH - Asatullayeva Mohinur (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: This article explores the use of interrogative pronouns in the English language. It examines their forms, functions, and syntactical positions in interrogative sentences. The study highlights common errors learners make and provides examples of correct usage. The research aims to contribute to a better understanding of English question formation and enhance language teaching methodologies.